In vitro effect of antiretroviral drugs on cultured primary astrocytes: analysis of neurotoxicity and matrix metalloproteinase inhibition. Issue 3 (9th January 2018) - Latronico, Tiziana; Pati, Ilaria; Ciavarella, Rossana; Fasano, Anna; Mengoni, Fabio; Lichtner, Miriam; Vullo, Vincenzo; Mastroianni, Claudio Maria; Liuzzi, Grazia Maria
Abstract: There is little information available on the possible toxic effects that antiretroviral (ARV) drugs used for the treatment of human immunodeficiency virus (HIV)‐infected subjects, may have on the central nervous system (CNS) resident cells. Moreover, it remains unclear whether the efficacy of the ARV drugs may also be due to their ability to exert extravirological effects on factors responsible for the development of HIV brain injury, e.g., matrix metalloproteinases (MMPs). This study investigates the toxicity of three different ARV drugs and on their ability to modulate levels and expression of gelatinases A (MMP‐2) and B (MMP‐9) in astrocytes. Primary cultures of rat astrocytes were activated by exposure to lipopolysaccaride (LPS) and simultaneously treated with darunavir, maraviroc, or raltegravir, used alone or in combination. Among the tested drugs, maraviroc was the less toxic for astrocytes. At toxic concentration (TC50 ), the studied drugs induced the production of reactive oxygen species (ROS), suggesting that the oxidative stress may represent a mechanism of ARV toxicity. As assessed by gelatin zymography and RT‐PCR, the single antiretroviral drugs reduced levels and expression of both MMP‐2 and MMP‐9 through the inhibition of the signaling transduction pathway of extracellular signal‐regulated kinase1/2, which is involved in the regulation of MMP‐9 gene. A synergistic inhibition of MMP‐2 and MMP‐9 was observed with combinations of the studied ARV drugs. The present results indicate that maraviroc, darunavir, and raltegravir, through their ability to inhibit MMP‐2 and MMP‐9 at doses non‐toxic for astrocytes, might have a great potential for the management of HIV‐associated neurological complications. Abstract : The potential impact of long‐term exposure to antiretroviral (ARV) drugs on the HIV‐neurological impairment is an area of active investigation. We provided evidence that the ARVs darunavir, raltegravir, and maraviroc are not toxic ' in vitro ' for astrocytes and inhibit the production of matrix metalloproteinases (MMP)‐2 and ‐9 through inhibition of ERK signaling pathway, which is involved in the regulation of MMP gene. These results might have a great potential for the management of HIV‐associated neurological complications.